Bridging Literacy Gaps Through Mobile Phones: Learners’ Perspectives in Non-Formal Settings - Mahpara Saleh, (IJLTP, 2025)
The present study intended to determine “Bridging Literacy Gaps Through Mobile Phones: Learners’ Perspectives in Non-Formal Settings”. The objectives of the study were to a) explore students’ perceptions towards use of mobile in enhancement of reading activities; b) sightsee students’ views on mobile phone use to improve vocabulary; and c) explore students’ perceptions towards use of mobile phone to enhance their pronunciation. This study employed a quantitative approach in which survey was utilized. The population of study comprised of students of Allama Iqbal Open University from B.Ed 1.5 years program. A randomly selected sample of 100 students was approached through an online survey. A self-developed questionnaire with extensive effort by focusing on the psychometric properties of the scale and sought expert opinion on it. This scale was based upon the objectives of the study. The tool was in 3-point Likert scale consisting of items on three dimensions of literacy (reading activities, vocabulary and pronunciation skills). Findings of the study indicated that most of the respondents agreed that mobile phone usage increased their reading literacy skills i.e. reading new books, reading vocabulary, downloading notes for reading, and upgrading reading pronunciation through the user-friendly mode of mobile. So, mobile devices are increasingly becoming the knowledge gateways to ensure universal useableness and user-friendliness that is necessary to cultivate inclusive digital learning platforms. However, those who did not agree with it exposed a critical digital divide that may be tackled by combining not only technology design but also ensuring policy reforms. Moreover, in distance learning, mobile phones may be encouraged by user-friendly, evidence-based, apps to enhance literacy skills.